2008
DOI: 10.1016/j.str.2008.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Dipeptide Epimerase Enzymatic Function Guided by Homology Modeling and Virtual Screening

Abstract: SUMMARY We have developed a computational approach to aid the assignment of enzymatic function for uncharacterized proteins that uses homology modeling to predict the structure of the binding site and in silico docking to identify potential substrates. We apply this method to proteins in the functionally diverse enolase superfamily that are homologous to the characterized L-Ala-D/L-Glu epimerase from Bacillus subtilis. In particular, a protein from Thermotoga martima was predicted to have different substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…The computational modeling suggested that a group of enzymes, distantly (approximately 30% sequence identity) related to the B. subtilis AEE, would be specific for hydrophobic dipeptides. One of these dipeptide epimerases, from T. maritima, was reported previously (9); to show specificity for L-Ala-L-Phe and similar dipeptides. Four of the predicted hydrophobic dipeptide epimerases belong to a group that includes a number of plant enzymes (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The computational modeling suggested that a group of enzymes, distantly (approximately 30% sequence identity) related to the B. subtilis AEE, would be specific for hydrophobic dipeptides. One of these dipeptide epimerases, from T. maritima, was reported previously (9); to show specificity for L-Ala-L-Phe and similar dipeptides. Four of the predicted hydrophobic dipeptide epimerases belong to a group that includes a number of plant enzymes (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…To provide specific predictions of substrate specificity, we used virtual library screening against the solvent-sequestered active site, which provides a defined cavity for the substrate. We previously reported computational predictions and in vitro screening to assign the L-Ala-D/L-Phe epimerase activity to a protein from Thermotoga maritima (gi:156442781; TM006) (9). In addition, the N-succinylArg racemase function was assigned to an enzyme from Bacillus cereus that clustered phylogenetically with the dipeptide epimerases (10).…”
mentioning
confidence: 99%
“…S1). Like most other members of the enolase superfamily, the five enzymes from the NSAR/OSBS subfamily are multimers (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The three previously characterized NSAR/OSBS subfamily enzymes are (53).…”
Section: Resultsmentioning
confidence: 97%
“…To visualize relationships between members of the subgroup, we generated sequence similarity networks using Pythoscape (16), where nodes represent sequences, and edges represent pairwise local alignments with BLAST e-values more significant than a specified cutoff, allowing a dynamic view of clustering patterns and sequence annotations. Sequence-similarity networks can handle thousands of sequences, are quick to compute and robust to missing data (17,18), and have been shown to correlate well with phylogenetic trees (19,20). Fig.…”
Section: Resultsmentioning
confidence: 99%